Tuned in, turned on exposure to pornographic materials as a correlate of early sexual initiation among Filipino adolescents - Laguna, Elma P.; Pagaduan, Antonio Jesus P. II (2005)
This study tackles the issue of how the media affect the sexual behavior of people. Using data from the 2002 Young Adult Fertility and Sexuality survey (YAFS3) and through bivariate and logistic regression analyses, it specifically examines the possible influence of exposure to pornographic media content on the Filipino adolescents' sexual initiation. Results of the analyses show substantial level of premarital sex involvement among the youth, as well as a significant difference between the males' and females' level and timing of premarital sex. Findings also indicate that to a certain extent, exposure to pornographic media is indeed associated with early initiation into sex.